QUANTIFIED CHARACTERIZATION OF SOIL BIOLOGICAL ACTIVITY UNDER CROP CULTIVATION - Wolinska, Agnieszka; Szafranek-Nakonieczna, Anna; Zielenkiewicz, Urszula; Tomczyk-zak, Karolina (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
Soil biological activity is extremely important for sustaining high soil fertility, crop yields, and therefore can effect economy. Poland is particularly relevant example where approx. 60% of land is used for crop cultivation. It is expected that agricultural soils contain much smaller number of microorganisms relative to non-cultivated soils. We hypothesise that agricultural soils are biologically degraded and cannot naturally regenerate which in turn may lead to relative infertility. The aim of the study was to evaluate which crop cultivation, oat or triticale, is more favourable for sustaining soil microbiological activity. Eight different cultivated soils and the same number of non-cultivated (control) soils were selected for the study. Soil samples were extracted from the surface layer, and taken to laboratory for determination of the: pH, total carbon (TC), permanganate oxidizable carbon (POXC), phosphate phosphorus (PO4-P) and total nitrogen (TN) content, microbial biomass (MB), soil respiration (SR), dehydrogenase activity (DHA) and DNA content. Spearmans rho correlation coefficient was used to assess multicolinearity between the above physico-chemical and biological soil properties. Our data suggest that cultivated soils are biologically degraded as reflected by lower values of all microbiological parameters with relation to non-cultivated soils. In terms of cultivated crop type, we show that triticale is more favourable for sustaining soil microbiological activity than oat. Positive correlations suggest that pH, TC, POXC, P, N content are the critical factors determining soil microbiological activities.